Possible Tsunami-Induced Sediment Transport From Coral Reef to Deep Sea Through Submarine Canyons on the Southern Ryukyu Forearc, Japan - Ikehara, Ken; Kanamatsu, Toshiya; Usami, Kazuko (Frontiers in Earth Science, 2022)
Submarine canyons are efficient sediment transport pathways from shallow marine areas to deep sea. Along active margins, large tsunamis are a trigger for sediment transport to deep sea. However, sediment transport through submarine canyons by such extreme wave events in the carbonate depositional environments has not been fully understood. Large tsunamis have repeatedly struck the coral reef islands of the southern Ryukyu Islands and have transported large boulders composed of coral from the reef to shore. In this study, we examined sediment cores collected near the mouths of submarine canyons and basin floor on the southern Ryukyu arc’s forearc. The presence of coarse calciturbidites containing coral, molluskan fragments, and coral reef benthic foraminifera was limited on the submarine fan formed at the mouth of the reef-connected and shelf-incised submarine canyon. In cores collected near the mouth of shelf-incised submarine canyons with no reef connection and slope-confined canyons, no coarse calciturbidite is observed. Few calciturbidites were found in more downslope cores, implying that most calcareous grains derived from shallow marine areas were deposited on this fan. Depositional intervals of turbidites were calculated to be several hundred–a few thousand years, which agree with the recurrence intervals of large tsunamis estimated from onshore tsunami deposits, based on radiocarbon dates in hemipelagic mud intervals. No temporal change in the depositional intervals of calciturbidites in the cores from the submarine fan since the last glacial maximum. Therefore, the tsunamis may be an important mechanism for surface sediment reworking in coral reefs, and shelf-incised and reef-connected submarine canyons can play an important role in the efficient transport of shallow marine calcareous grains to the deep sea.